Earnings management detection and its impact on european funds: a data analytics approach - Fernandes, S. Ribeiro; Laureano, Raul M. S.; Catarina Abrantes; Laureano, L. (2021 16th Iberian Conference on Information Systems and Technologies (CISTI), 2021)
Abstract: Portugal will receive €66.2 billion from the European Union in the coming years, with €45 billion to mitigate the impact of the pandemic on the economy and €21.2 billion from the next Community framework 2021-2027. But the success of allocating European funds to SMEs and the impact on the economy remains under discussion, making it urgent to find efficient and effective solutions for the benefit of the Portuguese economy. Thus, how can the earnings management combined with Analytics techniques benefit the process of allocating financial funds to Portuguese SMEs? To answer the question formulated, the Beneish M-Score model was used, in combination with data analysis and Decision Trees - CART and CHAID, with the objective of predicting the success of projects to European Union funds. The results are promising, by identifying as good predictors the Beneish M-Score indices of the success of SME investment projects at the time of application. Thus, the management bodies of the European funds gain insights into the importance that the manipulation of results can have in the approval of project applications, but not if it is subsequently reflected in this funding in successful projects. Resumo: Portugal nos próximos anos vai receber, 66,2 mil milhões de euros da União Europeia, sendo 45 mil milhões para atenuar o impacto da pandemia na economia e 21,2 mil milhões do próximo quadro comunitário 2021-2027. Mas o sucesso da atribuição dos fundos europeus às PME e o impacto na economia continua a estar em debate, tornando-se urgente encontrar soluções eficientes e eficazes para o benefício da economia portuguesa. Assim, como podem as técnicas analíticas de deteção de manipulação de resultados e de análise preditiva beneficiar o processo de atribuição de fundos financeiros às PME portuguesas? Para responder à questão utilizou-se o modelo M-Score de Beneish combinado com árvores de classificação (CART e CHAID) com o objetivo de prever o sucesso dos projetos financiados por fundos da União Europeia. Os resultados são promissores, ao identificar como bons preditores do sucesso dos projetos de investimentos das PME, à data da candidatura, os índices M-Score. Assim, os organismos gestores dos fundos europeus ganham insights relativos à importância que a manipulação de resultados pode ter na aprovação das candidaturas de projetos, mas não se refletindo, posteriormente, esse financiamento em projetos de sucesso.